Perancangan Media Promosi Produk Sembako UD. Boru Lubis Berbasis Animasi 3D Menggunakan Karakter Metode Lowpoly - Siti Aisyah Lubis (UIN Sumatera Utara, 2022)
The development of visual communication media at this time helps in supporting information and communication. However, often the visual communication media presented are less effective and efficient. With 3D animation media, 3D animation media is considered effective enough to attract customer interest, because 3D animation is quite popular among all circles. The presentation of attractive and entertaining advertising media will encourage the wider community to shop. This is evidence that the design of a work of art is improving so that it can keep up with the rapid development of technology. UD. Boru Lubis (icha lubis shop) engaged in the trade of basic necessities is considered necessary to have an attractive promotional media and can be a medium of information, especially for consumers. It is hoped that this promotional media will be useful for UD. Boru Lubis especially for potential customers. Keywords: Promotional Media, 3D Animation, information.